Application and advantages of auricular acupoint pressing therapy in patients with diseases of the digestive system (耳穴压丸在消化系统疾病中的应用及优势) - JI Zhi (姬陟); KONG Huihua (孔会华); LI Ning (李宁); LI Yueru (李月茹); LI Jing (李静); CAO Hongjing (曹红京) (中西医结合护理)
Diseases of the digestive system are common in clinical practice, seriously affecting people's health and quality of life. Auricular acupoint pressing therapy has certain advantages in relieving symptoms of digestive disorders such as stomach pain, eructation and constipation. This paper reviewed studies on application and advantages of auricular acupoint pressing therapy in patients with diseases of the digestive system, and provided clinical practice of integrated traditional Chinese and western medicine nursing on the diseases of the digestive system. (消化系统疾病是临床常见病和多发病, 严重影响人们的健康和生活质量。耳穴压丸在缓解胃痛、呃逆、便秘等消化系统疾病症状方面有一定特色和优势。本研究就耳穴压丸在消化系统疾病中的应用进展进行综述, 总结特色和优势, 旨在为中西医结合干预提供参考。)